Lukàcs and the issue of democracy as a strategy - Roio, Marcos Del [UNESP] (My University, 2021)
The question of strategy firstly appears on Lukács' thought on the so-called Blum Theses, written towards the end of 1928 as a formula against bourgeoise domination, further developed between 1945-47, phase of the new democracy as the path for overcoming Capitalism. Lukács also develops a reflection about socialist democratization as a formula to destroy the bureaucracy that had germinated, becoming power and habit in socialist experiences.
Lukàcs e a questão da democracia como estratégia
Keywords: Democratic dictatorship; New democracy; Socialist democratization; Stalinism